KONSEP PEMIKIRAN PENDIDIKAN ISLAM MENURUT FAZLUR RAHMAN - Nanang Ardiansyah; Umam Mufti; Wantini Wantini (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTFazlur Rahman is an Islamic thinker who has a major influence on the development ofscience. Fazlur Rahman's concept of education rests on the concept and collaborativeapproach between modern and philosophical studies based on the Qur'an and Sunnah.Through this approach, directing the vision of the purpose of Islamic education is idealand practical. The research method used in this writing is a critical historical method.Based on the research results from the library that Fazlur Rahman was a big figure ofthe Islamic world. Fazlur Rahman argues that education seeks to produce a societythat is able to integrate modern education based on the Qur'an and Sunnah and seeksto preserve the existence of the future society.Keywords: education thoughts, Fazlur Rahman.